Analysis of the causes of engineering structures deformations at gas industry facilities in the permafrost zone - Gennadii G. Vasiliev; Anton A. Dzhaljabov; Igor A. Leonovich (Записки Горного института, 2021)
Construction of oil and gas infrastructure facilities on permafrost soils is the most important task of increasing the raw material base of the entire fuel and energy industry in Russia. Permafrost soil is a complex, multicomponent system, state of which depends on many factors. Buildings and structures built under such conditions, on the one hand, have a complex thermal effect on permafrost soils, and on the other hand, they perceive the consequences of changes in the characteristics of such soils. This situation leads to the fact that buildings and structures on permafrost soil during their life cycle are subject to complex and poorly predictable deformations. Article presents the results of a study for various degradation processes of permafrost soils that can be implemented at construction sites of industrial facilities. Analysis of the deformations causes for engineering structures at the gas industry in the permafrost zone is carried out. Series of reasons causing such deformations have been investigated. Comprehensive criterion for assessing changes in permafrost-geological conditions of industrial sites is proposed. It is suggested to apply the method of calculating the individual characteristics for the temperature regime of the territory to monitor and assess the conditions of heat exchange and predict changes in the geocryological conditions of permafrost soil.